Using specific test to access for initial teacher training. - Pérez-Granados, Laura (Universidad de Granada, 2018)
Over recent years Finland has led the way in international research and studies into teacher recruitment and training. The number of people wishing to do a degree in teaching far exceeds the number of places available, meaning that universities set very high standards when selecting students. Having an understanding of the entry procedure for the most exemplary teacher education courses in the world could help us to identify the keys to success when choosing the most suitable prospective teachers and also to find new ways of carrying out the university admissions process in Spain and in other countries in Europe. In this regard, we focus on the following aspects: What would happen if we applied Finnish standards to students just starting their teaching degrees? What type of knowledge and/or personal dispositions should be taken into account when selecting prospective teachers? This article aims to show the results attained after recreating the Finnish selection procedure for teaching degree students, in this case involving a sample of students from the Faculty of Education Sciences of the University of Malaga. The results show that none of the students in the sample responded positively to the different tests they undertook.
La utilización de pruebas específicas para acceder a la formación inicial del profesorado.
Política de acceso abierto tomada de: https://jett.labosfor.com/index.php/jett/about
Keywords: Profesores - Formación profesional; Investigación activa en educación; Formación docente; Educación Superior; Acceso a la universidad; Competencias docentes